2003
DOI: 10.1055/s-2003-37202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Aerobic Exercise on Microcirculatory Flow and Nitric Oxide in Humans

Abstract: In the present study we assessed the effect of physical training on Laser Doppler skin flux (LDF) and nitric oxide (NO) release, before and after 3 min of brachial artery occlusion. To this end we performed laser Doppler measurements and the venous plasma assay of nitrite/nitrate (NOx) on 10 sedentary healthy subjects and 10 endurance athletes. The sedentary control subjects had lower basal and post reperfusion levels of NOx as compared to athletes (mean +/- SE: 27.8 +/- 3.5 vs. 33.2 +/- 3.4, 48.6 +/- 7.9 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 24 publications
(49 reference statements)
9
40
1
Order By: Relevance
“…This may be explained by the elevated baseline plasma [NO 3 − ] and [NO 2 − ] in this cohort (Vassalle et al 2003), although multiple other factors may also be important (Jones 2014). It is therefore unclear whether the reduced effects of NO 3 − supplementation reported during longer vs. shorter duration exercise tests are related to the exercise duration (and requisite work rate) or the high training status of subjects in these investigations (Bescós et al 2012;Wilkerson et al 2012;Cermak et al 2012b;Lane et al 2014;Glaister et al 2015).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This may be explained by the elevated baseline plasma [NO 3 − ] and [NO 2 − ] in this cohort (Vassalle et al 2003), although multiple other factors may also be important (Jones 2014). It is therefore unclear whether the reduced effects of NO 3 − supplementation reported during longer vs. shorter duration exercise tests are related to the exercise duration (and requisite work rate) or the high training status of subjects in these investigations (Bescós et al 2012;Wilkerson et al 2012;Cermak et al 2012b;Lane et al 2014;Glaister et al 2015).…”
Section: Introductionmentioning
confidence: 81%
“…well-trained and elite athletes) (VO 2max >70 ml·kg −1 ·min −1 ) (Peacock et al 2012;Bescós et al 2012;Christensen et al 2013;Porcelli et al 2014;Sandbakk et al 2015). These highly trained athletes manifest a host of different characteristics likely to diminish their responsiveness to NO 3 − supplementation (for review, see Jones 2014), including elevated endogenous NO 3 − and NO 2 − reserves (Vassalle et al 2003).…”
Section: Effects Of Brj On 1500 M Tt Performancementioning
confidence: 99%
“…(Wang, 2005). Also, Vassalle et al have shown an enhanced release of NO in the trained combined to an increased LDF response induced by PRH (Vassalle et al, 2003). Increased NO might be due to an upregulation of eNOS or its enhanced activity.…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 98%
“…Conversely, studies in well-trained individuals exercising in hypoxia have typically found no effect of nitrate supplementation [38][39][40]. Well-trained individuals exhibit increased presence and activity of the NOS enzymes [31]; possess higher baseline nitrate/nitrite concentration [29]; may habitually consume high levels of nitrate as a consequence of their large daily energy intake [30]; and experience lower tissue acidosis and hypoxia [20] relative to the untrained. Moreover, a recent investigation in normoxia observed an inverse correlation between aerobic fitness and the response to nitrate supplementation [17].…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 99%
“…Conversely, well-trained participants (V O2max > 60 ml·kg -1 ·min -1 ) are typically less responsive to dietary nitrate supplementation [17,[19][20][21][25][26][27], even when very high nitrate doses (~ 19.5 mmol) are administered [28]. Highly-trained individuals are known to possess elevated baseline nitrate/ nitrite reserves [29], may habitually consume large amounts of nitrate, subsequent to their increased calorie consumption [30], and exhibit greater presence and activity of the NOS enzymes, relative to the untrained [31]. Such differences may reasonably be expected to lessen the ergogenic effect of nitrate supplementation [30].…”
Section: Introductionmentioning
confidence: 99%